Complex Regional Pain Syndrome: Epidemiologic Features, Treatment Approaches, Workday Loss and Return to Work/Disability Ratios - Mehmet Zeki Kıralp,; Ümit Dinçer,; Engin Çakar,; Hasan Dursun, (Archives of Rheumatology, 2009)
Objective: The aim of this study was to assess the epidemiologic features of complex regional pain syndrome (CRPS) and the effectiveness of the treatment approaches and to investigate its effects on working life. Material and Methods: The medical records of 106 consecutive patients who were diagnosed with CRPS were reviewed retrospectively regarding demographics, inciting events and injury sites, duration of symptoms, radiologic signs (direct roentgenogram, scintigraphy), treatment modalities, duration of hospitalization, workday loss, treatment outcomes, and disability as a sequela. Results: The most common inciting events were fracture and soft tissue injuries. The mean duration of symptoms was 4.1±3.0 months and of workday loss was 187.5±107.4 days. The clinical outcome in 93 patients (87.7%) was sufficient enough to enable patients to return to their previous work after the rehabilitation program. Conclusion: The management period of CRPS is usually long and causes high workday loss; some patients became disabled despite all therapeutic interventions. (Turk J Rheumatol 2009; 24: 1-5)